Analisis Teknik dan Hasil Tata Rias Wajah antara Makeup Natural dan Glam Look - Intan Santika Permatasari; Bunga Julian Sunaryo; Nabila Azzahra; Mutiara Putri Setyawan; Lailatul Habibah; Anik Maghfiroh (Lembaga Pendidikan, Penelitian, dan Pengabdian Kamandanu, 2026)
Natural makeup and glam makeup are derived from different makeup techniques. Makeup, as the art of transforming appearance using cosmetics, is influenced by global trends such as Korean beauty for natural makeup and the Western entertainment industry for glam makeup. This study uses a descriptive qualitative approach with a feminist framework and a cultural studies perspective. The results show that natural makeup emphasizes simplicity with lightweight products like BB cream and lip tint, suitable for everyday activities, representing authenticity and psychological comfort. In contrast, glam makeup focuses on drama using full-coverage foundation and bold eyeshadow, ideal for formal events, a symbol of luxury and performativity. The comparison reveals differences in application, products, and cultural meanings, where natural makeup rejects excessiveness, while glam makeup is associated with capitalism and patriarchy. The conclusion emphasizes makeup as a medium for identity construction, encouraging wise choices for authentic empowerment.